2017
DOI: 10.18544/pedm-23.01.0068
|View full text |Cite
|
Sign up to set email alerts
|

Potential Clinical Benefits of a Two-bag System for Fluid Management in Pediatric Intensive Care Unit Patients with Diabetic Ketoacidosis

Abstract: The two-bag system is associated with lower incidence of hypoglycemia and faster discharge from the PICU. We recommend that clinicians consider using the two-bag system for fluid management in pediatric patients with diabetic ketoacidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Furthermore, the length of the PICU stay and hospital length of stay were also not different between the groups. This is in contradiction to the study of Velasco et al 14 that demonstrated that the two bag system was associated with fewer hours of PICU stay compared to the one bag system. It is possible that the conflicting results may be related to the variations in the definitions of LOS and the variations in the transfer policies of patients with DKA from the PICU to a pediatric ward.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, the length of the PICU stay and hospital length of stay were also not different between the groups. This is in contradiction to the study of Velasco et al 14 that demonstrated that the two bag system was associated with fewer hours of PICU stay compared to the one bag system. It is possible that the conflicting results may be related to the variations in the definitions of LOS and the variations in the transfer policies of patients with DKA from the PICU to a pediatric ward.…”
Section: Discussioncontrasting
confidence: 96%
“…This accomplishment occurred through use of standardized DKA guidelines built on a two-bag fluid system, standardization of hand-offs, inclusion and education of all stakeholders, and explicit EMR orders to support clinical practice. While previous retrospective studies evaluating use of standardized management of DKA with or without two bag fluid system indicate the potential for decreased cost, 4,13,14 more rapid DKA resolution, 5,15 and/or decreased rates of hypoglycemia 5,7,8 ; to our knowledge, our study is the first to demonstrate how various tenets of quality improvement science can be prospectively paired with the implementation of standardized DKA guidelines based on a two-bag fluid system with the primary objective to decrease the rate of low BGs in pediatric patients with DKA.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have concluded two bag-fluid systems, as compared to traditional single IV bag treatment methods, allow for quicker resolution of acidosis 5,6 and decreased rates of hypoglycemia. 5,7,8 However, no previous studies have prospectively implemented standardized DKA guidelines built on a two-bag system with the primary objective to reduce the occurrence of low blood glucoses (i.e., BG < 80 mg/dl).…”
Section: Piloting Of 6 Th Guidelines and Increased Incident Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the initial fluid, all the patients received isotonic fluid (0.9% saline) solution for a duration of 4 hours followed by a fluid solution consisting of 0.45% saline, with an aim to correct the dehydration over 48 hours. We use the two-bag system for fluid management in DKA patients in our unit [30]. Insulin infusion was started after 1 hour, upon the completion of initial fluid therapy.…”
Section: Treatment Protocol-mentioning
confidence: 99%